1959
DOI: 10.1002/pol.1959.1203512816
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering of isotactic polystyrene

Abstract: Results of light scattering as well as viscosity measurements on a series of isotactic polystyrene fractions, and on a sample of unfractionated isotactic polymer in toluene at 30°C. are reported. The results are in agreement with the conclusion of Natta, Danusso, and Moraglio that no difference exists between the viscometric behavior of atactic and isotactic polystyrene; the same seems to hold also for the molecular dimensions. The ratio A2M/[η] for isotactic polystyrene is lower than for atactic fractions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1961
1961
1999
1999

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…For the polymerization of unsymmetrical unconjugated dienes, Trossarelli et al 8 have reported the kinetics of cyclopolymerization which has been further developed for simplification by the present authors.' In this work we treat the cyclopolymerization of DAM, the mechanism of which is essentially equivalent to that of unsymmetrical unconjugated dienes except the bicyclo-propagation reaction.…”
Section: Polymerization Kineticsmentioning
confidence: 94%
“…For the polymerization of unsymmetrical unconjugated dienes, Trossarelli et al 8 have reported the kinetics of cyclopolymerization which has been further developed for simplification by the present authors.' In this work we treat the cyclopolymerization of DAM, the mechanism of which is essentially equivalent to that of unsymmetrical unconjugated dienes except the bicyclo-propagation reaction.…”
Section: Polymerization Kineticsmentioning
confidence: 94%
“…The majority of this work has involved the measurement of intrinsic viscosities, molecular sizes and second virial coefficients in thermodynamically good solvents. [2][3][4][5][6][7][8][9][10][11] The conclusions drawn from these investigations are that the perturbed molecular dimensions in good solvents are indistinguishable for the atactic and isotactic forms, but that the stereoregular polymers exhibit smaller second virial coefficients (at least for lower molecular weights) in these solvents. This latter conclusion is in agreement with the earlier work of Muthana and Mark,12 who compared crystalline and amorphous samples of poly-(vinyl isobutyl ether).…”
Section: Introductionmentioning
confidence: 99%
“…We can suppose that the some sequence of monomer units interacts with the solvent molecule and the sequence distribution differences between two polymer types as demonstrated in Table II bring about the large differences in B parameters, especially in 67 wt% aq nitric acid. On the 9th and lOth columns of Table VI collects, the steric factor 0', is defined as (12) (where Ar is A of a hypothetical chain with free internal rotation (model I) and Ar = 0.423 x w-s em for PAN) and the characteristic ratio Coo is given by (13) (where Mb is the mean molecular weight per skeletal bond ( =26.5) and I is the mean bond length (1.54 x w-s em), both calculated from the most probable A value). Figure 12 shows the effect of the side chain molecular weight on 0' of the vinyl-type polymers.…”
Section: Dmso A(y-pan)>a(r-pan) and B(y-pan)['1](r-pan) In 67 Wt% Amentioning
confidence: 99%